The Jackal's Mistress : a novel - Bohjalian, Chris, 1962- (New York : Doubleday, 2025)
"In this Civil War love story, inspired by a real-life friendship across enemy lines, the wife of a missing Confederate soldier discovers a wounded Yankee officer and must decide what she's willing to risk for the life of a stranger, from the New York Times bestselling author of such acclaimed historical fiction as Hour of the Witch and The Sandcastle Girls. Virginia, 1864-Libby Steadman's husband has been away for so long that she can barely conjure his voice in her dreams. While she longs for him in the night, fearing him dead in a Union prison camp, her days are spent running a gristmill with her teenage niece, a hired hand, and his wife, all the grain they can produce requisitioned by the Confederate Army. It's an uneasy life in the Shenandoah Valley, the territory frequently changing hands, control swinging back and forth like a pendulum between North and South, and Libby awakens every morning expecting to see her land a battlefield. And then she finds a gravely injured Union officer left for dead in a neighbor's house, the bones of his hand and leg shattered. Captain Jonathan Weybridge of the Vermont Brigade is her enemy-but he's also a human being, and Libby must make a terrible decision: Does she leave him to die alone? Or does she risk treason and try to nurse him back to health? And if she succeeds, does she try to secretly bring him across Union lines, where she might negotiate a trade for news of her own husband? A vivid and sweeping story of two people navigating the boundaries of love and humanity in a landscape of brutal violence, The Jackal's Mistress is a heart-stopping new novel, based on a largely unknown piece of American history, from one of our greatest storytellers"--.
new book 2025 spring.
Keywords: Historical fiction; General; Suspense fiction; Shenandoah Valley Campaign, 1864 (May-August) -- Fiction; Shenandoah Valley Campaign, 1864 (August-November) -- Fiction; Virginia -- History -- Civil War, 1861-1865 -- Campaigns -- Fiction; Historical fiction; Novels; Romance fiction